PENGGUNAAN LEMBAR KERJA PESERTA DIDIK (LKPD) SEBAGAI MEDIA PEMBELAJARAN UNTUK MENINGKATKAN HASIL BELAJAR BAHASA INDONESIA PADA KELAS IV UPT SPF SDI PA’BAENG-BAENG - Indah Lestari Kiding Allo; Nur Izza (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
Based on the results of observations in classIV UPT SPF SDI PA'BAENG-BAENG, several problems were found, one of which was the rare use of interesting learning media so that students became a little bored and less motivated to learn so that the learning outcomes obtained were relatively low. The solution to improving student learning outcomes is to design more attractive LKPD learning media with brighter pictures, colors, writing and interesting learning activity directions. With this LKPD, students are more interested and enthusiastic about doing the tasks on the LKPD and make it easier for students to understand the material presented. This research aims to determine the improvement in learning outcomes of class IV students at UPT SPF SDI Pa'baeng-Baeng in Indonesian language subjects by using Student Worksheets (LKPD) as a learning medium. The type of research used is classroom action research (PTK). Based on the results of research data analysis, the results obtained from using LKPD in Indonesian language subjects can improve student learning outcomes in class IV UPT SPF SDI Pa'Baeng-Baeng. This is shown by the learning outcomes obtained by each individual increasing from pre-cycle, cycle 1 to cycle 2. In the pre-cycle, student learning outcomes are still very low with an average of 22.22% of students experiencing completeness. Meanwhile, in cycle 1 and cycle 2, the increase in student learning outcomes experienced a significant increase. In cycle 1, the presentation of students who had completed it was 61.11% but had not yet reached the criteria for success, while in cycle 2, the presentation of students was 83.33%. Who has achieved the success criteria.